2009
DOI: 10.1111/j.1099-0860.2008.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

From Policy to Practice: The Implementation and Negotiation of Technologies in Everyday Child Welfare

Abstract: A central element of the Every Child Matters reforms in England are measures which aim at improving information sharing. Amongst these are the children’s database and the Common Assessment Framework, both representing technological solutions to long‐standing concerns about information sharing in child welfare. This article reports some findings from an Economic and Social Research Council (ESRC)‐funded study which examined their introduction and use in everyday professional practice. Substantial differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
1
24
0
1
Order By: Relevance
“…Sharing information is, as we are all familiar with now after the advent of social networking, not always a good thing. For their program, the material was not always judged to be relevant (written for different audiences), it was not clear when each team member should use the tool, and so on (Peckover et al, 2009). Each of these difficulties point to the fact that rolling out such a system must be handled with sufficient foresight of the human interaction, social tendencies, and challenges that inhere in collaborative efforts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sharing information is, as we are all familiar with now after the advent of social networking, not always a good thing. For their program, the material was not always judged to be relevant (written for different audiences), it was not clear when each team member should use the tool, and so on (Peckover et al, 2009). Each of these difficulties point to the fact that rolling out such a system must be handled with sufficient foresight of the human interaction, social tendencies, and challenges that inhere in collaborative efforts.…”
Section: Discussionmentioning
confidence: 97%
“…In other words, there is difficulty that goes unseen and is not well understood because it offends our cultural sensibilities to admit that a process that we idealistically think should be objective is in fact very dependent upon individual personalities and intergroup dynamics. Peckover, Hall, & White (2009) described such difficulties that ultimately caused the failure of a child welfare database effort in England. Sharing information is, as we are all familiar with now after the advent of social networking, not always a good thing.…”
Section: Discussionmentioning
confidence: 98%
“…New technology, e.g. software to structure case records, has been widely introduced in many countries to facilitate good practice but there is a growing body of research giving detailed accounts of how it is, in practice, having negative effects and disrupting the reasoning processes of professionals (Bell, Shaw, Sinclair, Sloper, & Rafferty, 2007;Gillingham, 2009;Peckover & Hall, 2008). While many will agree that over-control is stifling good quality front-line work, it is not easy to change direction and move to a more reflective organisation able to support more creative and adaptive performance at the front line.…”
Section: A Systems Approach To Learningmentioning
confidence: 99%
“…An organisation that prioritises procedures runs the risk of undervaluing the professional skills needed to apply the procedures competently. In child protection work, evidence of this risk is seen in the reduced time workers have to spend with children and families (Peckover & Hall, 2008) it is desirable to have a rule. If, however, the desirable action is not so specific, then professional judgment will be more appropriate.…”
Section: The Cumulative Impactmentioning
confidence: 99%
“…1 Details of these studies can be found on the ESRC Society Today website, and in various publications (for example, Broadhurst et al, 2009;Peckover et al, 2008Peckover et al, , 2009Pithouse et al, 2009;White et al, 2009). We will draw on data from this research, together with governmentsponsored evaluations (Cleaver et al, 2004;Brandon et al, 2006;Bell et al, 2007), to examine the ways in which the technologies have been developed.…”
Section: Icts In Child Welfare In Englandmentioning
confidence: 99%